Artists' books for handheld mobile devices: Expanding the artist's book genre. Issue 1 (1st April 2017) - Mader-Meersman, Julie
This article examines the status of the artist's book genre within the digital media landscape. The genre has the potential for widespread public awareness by embracing new media and small-format, handheld mobile devices. The author highlights the void of artists' books and uses examples of existing book apps and other interactive artworks to arrive at the conclusion that digital media should be embraced within the artist's book genre. She also includes reflection on her own artist's book app creative research project, The Book Worm Tales, to share the process of transitioning her artistic experiments within the genre from print to screen. Inspired by an appreciation and concern for the biodegradation of rare physical books caused by moths and organisms such as mould, the project poetically reflects on rapid changes in book media, while preserving in virtual form experiential aspects of real, rare books in the process. The article includes the premise of that project; discussion of the experimentation involved in exploiting the creative potential of the medium; historical perspective on the materiality of the book; and implications of the digital medium on the artists' books genre.